Analysis of adverse effects of nitrates and nitrites with particular emphasis on methemoglobinemia and maculopathy based on clinical cases and publicly available literature - Gut, Michał Edward; Sowińska, Marta; Adamczyk, Aleksandra; Ważny, Maria; Gancarz, Agnieszka; Bezara, Damian; Żak, Agata; Toporowska-Kaźmierak, Joanna; Banasik, Mateusz; Tworek, Miłosz (Quality in Sport, 2026)
Background: Nitrates are currently one of the most commonly used drug classes in medical practice. The usefulness of nitroglycerin in the treatment of coronary artery disease is invaluable. Nitrates have also been used in other cardiac, gynecological, and gastrointestinal diseases. Aim: To draw attention to the problem of inappropriate recreational use of nitrates and nitrites by analyzing extreme cases and adverse reactions resulting from the use of these preparations. Materials and Methods: This article is a review of the publicly available literature from recent years (including case reports) regarding nitrates, their mechanisms of action, and adverse reactions, particularly maculopathy and methemoglobinemia. Results: Alkyl nitrites are a specific group of inhalant drugs that are readily available and legal in Poland. They have a similar mechanism of action to nitrates used in the treatment of the previously mentioned diseases, involving the supply of nitric oxide. In addition to mild reactions, adverse reactions such as dizziness and headache, may lead to maculopathy or methemoglobinemia in severe cases. Although the exact mechanism of action is unknown, it is thought to result from oxidative stress and vascular epithelium damage. Conclusions: The widespread availability of nitrite preparations on the market and the underestimated prevalence of recreational nitrite use should prompt primary care physicians to rapidly diagnose and initiate treatment when characteristic symptoms of nitrate toxicity occur.